SINERGITAS PERAN PEMERINTAH DESA DAN PEMUDA KARANG TARUNA DALAM PEMBANGUNAN DESA - Kusroh Lailiyah (Journal Legal Dialectics, 2023)
This research aims to find out the synergy between the role of the village government and youth organizations in village development. This research uses a qualitative approach through descriptive analysis methods based on literature studies obtained which are then used as analysis material. The results of this research show that as regulated in the regulation of the Minister of Social Affairs of the Republic of Indonesia Number: 77/HUK/2010 concerning Basic Guidelines for Karang Taruna Organizations, Karang Taruna Youth is a social organization as a place and means of development for every member of society, which grows and develops on the basis of awareness and social responsibility from, by and for the community, especially those engaged in social welfare efforts. To achieve this target, the main task of Karang Taruna is to work together with the village government and other components of society to find out how to overcome problems that occur in the community, especially those operating in the field or social welfare problems, especially those faced by many people. young generation, whether preventive, rehabilitative or developing the potential that exists in the young generation in their environment. Keywords: village development, village government, youth organization